Implementasi Gerakan Tujuh KAIH pada Kurikulum Merdeka untuk Penguatan Karakter Peserta Didik Sekolah Dasar - Teti Nurhasanah; Eva Dianawati Wasliman; Sri Handayani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the implementation of the Seven KAIH Movement (Habits of Great Indonesian Children) in strengthening the character of students at Cangkuang Elementary School, Majalaya District, Bandung Regency. This program is a positive habit-building initiative designed to shape the moral foundation of elementary school students through seven core values. The research method used was descriptive qualitative with a case study approach. Data collection was conducted through observation, interviews, and documentation of the school community at Cangkuang Elementary School. Data analysis included data reduction, presentation, and conclusion drawing. The results indicate that the implementation of the Seven KAIH Movement was carried out through integration into daily activities, teacher role models, and habit-based supervision. This program has been proven to have a significant impact on improving student discipline, independence, and polite behavior. Although there were challenges in consistent supervision outside of school, collaboration between teachers and parents was a key factor in the program's success. This study concludes that the Seven KAIH Movement is an effective instrument for internalizing character values ​​if implemented systematically and sustainably.